The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1109/jstqe.2020.3022948
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Perspective on Optical Phased Array for Automotive LiDAR

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(98 citation statements)
references
References 113 publications
0
80
0
Order By: Relevance
“…The points detected in vehicle proximity (between 0m-20m) are mainly ground points, conversely points in the regions 20m-30m, 40m-50m, and 70m-80m represent the objects in the scene. It is worth noting that the number of ground points decreases steeply when the distance increases, and also that due to the resolution and accuracy degradation with the distance [2].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The points detected in vehicle proximity (between 0m-20m) are mainly ground points, conversely points in the regions 20m-30m, 40m-50m, and 70m-80m represent the objects in the scene. It is worth noting that the number of ground points decreases steeply when the distance increases, and also that due to the resolution and accuracy degradation with the distance [2].…”
Section: Resultsmentioning
confidence: 99%
“…This technique also enables relative velocity to be determined through the Doppler shift [24]. A recent in depth review on LiDAR technologies and its working principles can be found in [2].…”
Section: ) Frequency Modulated Continuous Wave (Fmcw)mentioning
confidence: 99%
See 2 more Smart Citations
“…The radiation length of 1.47 mm yields a corresponding 3-dB beamwidth of 0.052° in the far-field region at the wavelength of 1.55 μm. Such narrow beam width is very favorable for automotive LiDAR applications where an angular resolution around 0.1° is required for distinguishing any potential hazards even at a distance of 200 m [30,31].…”
Section: B Radiation Rates and Frequency-scanning Characteristicsmentioning
confidence: 99%